Czy wiemy jak wspierać ucznia-sportowca w polskiej szkole? - Iwanowska, Zofia (Studia Edukacyjne, 2025)
All students need tailored support. While most children and adolescents share similar life experiences, there is a big focus on adjusting schools and education to the needs of the majority. This paper, however, investigates the life of a minority of student-athletes whose everyday life differs from what most experience. The text shows the context of those students’ educational and sports life and the challenges they might be facing. In addition, it investigates teachers’ knowledge about student-athletes and their situation at school. It concludes that much more research needs to be done, especially on sharing a Polish student-athlete’s perspective. Knowledge of good practices regarding supporting this group in Polish schools should also be shared with the wider public.